Compressional intracontinental orogens: Ancient and modern perspectives - Raimondo, T.; Hand, M.; Collins, William (Elsevier BV, 2014)
Compressional intracontinental orogens are major zones of crustal thickening produced at large distances from active plate boundaries. Consequently, any account of their initiation and subsequent evolution must be framed outside conventional plate tectonics theory, which can only explain the proximal effects of convergent plate-margin interactions. This review considers a range of hypotheses regarding the origins and transmission of compressive stresses in intraplate settings. Both plate-boundary and intraplate stress sources are investigated as potential driving forces, and their relationship to rheological models of the lithosphere is addressed. The controls on strain localisation are then evaluated, focusing on the response of the lithosphere to the weakening effects of structural, thermal and fluid processes. With reference to the characteristic features of intracontinental orogens in central Asia (the Tien Shan) and central Australia (the Petermann and Alice Springs Orogens), it is argued that their formation is largely driven by in-plane stresses generated at plate boundaries, with the lithosphere acting as an effective stress guide. This implies a strong lithospheric mantle rheology, in order to account for far-field stress propagation through the discontinuous upper crust and to enable the support of thick uplifted crustal wedges. Alternative models of intraplate stress generation, primarily involving mantle downwelling, are rejected on the grounds that their predicted temporal and spatial scales for orogenesis are inconsistent with the observed records of deformation. Finally, inherited mechanical weaknesses, thick sedimentary blanketing over a strongly heat-producing crust, and pervasive reaction softening of deep fault networks are identified as important and interrelated controls on the ability of the lithosphere to accommodate rather than transmit stress. These effects ultimately produce orogenic zones with architectural features and evolutionary histories strongly reminiscent of typical collisional belts, suggesting that the deformational response of continental crust is remarkably similar in different tectonic settings.